Setting of import tolerances for sulfoxaflor in various crops - EFSA (European Food Safety Authority); Giulia Bellisai; Giovanni Bernasconi; Alba Brancato; Luis Carrasco Cabrera; Irene Castellan; Monica Del Aguila; Lucien Ferreira; German Giner Santonja; Luna Greco; Samira Jarrah; Renata Leuschner; et al. (EFSA Journal, 2023)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Dow AgroSciences Ltd submitted a request to the competent national authority in Greece to set an import tolerance for the active substance sulfoxaflor in various crops. The data submitted in support of the request were found to be sufficient to derive import tolerance proposals for cane fruits, blueberries, avocados, mangoes, pineapples, asparagus, globe artichokes, sunflower seeds and coffee beans. Adequate analytical methods for enforcement are available to control the residues of sulfoxaflor in plant matrices under consideration at the validated LOQ of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of sulfoxaflor according to the reported agricultural practices is unlikely to present a risk to consumer health.